Inhibition of miR-621 expression promotes proliferation, migration and invasion of human gastric cancer cell lines - CHEN Guo-yan, FENG Xiao-bo (Jichu yixue yu linchuang, 2020)
Objective To detect the expression of miR-621 in gastric cancer tissues and cell lines and to evaluate the prognostic significance of miR-621, and to analyze the effect of miR-621 on the biological function of gastric cancer cells. Methods Expression of miR-621 in cancer tissue and cell lines was detected by real-time polymorperase chain reaction(RT-qPCR). Chi-square test was used to analyze the relationship between miR-621 and clinical pathological features of gastric cancer patients. Prognostic significance of miR-621 for gastric cancer was analyzed by survival curve and Cox regression. Finally, human gastric cancer cells were transfected with miR-621 mimics and inhibitors to analyze the proliferation, migration and invasion ability of gastric cancer cells. Results The expression of miR-621 was significantly downregulated in gastric cancer tissues and cell lines as compared to the adjacent tissues and gastric mucosa cell lines(P＜0.01), and low expression was associated with lymph node metastasis, tumor differentiation, and TNM stage in gastric cancer(P＜0.05). The patients with low expression of miR-621 had a poor overall survival rates(log-rank test P＜0.001), and miR-621 was an independent prognostic indicator for gastric cancer patients(HR=3.09, 95% CI=1.31-7.27, P=0.01). In addition, low-expression of miR-621 significantly increased proliferation, migration, and invasion of gastric cancer cells(P＜0.05). Conclusions Low expression of miR-621 is associated with poor prognosis of gastric cancer, which promotes the proliferation, migration and invasion of gastric cancer cells.